Economic Framework of Membrane Technologies for Natural Gas Applications. Issue 4 (2nd October 2019) - Martin-Gil, V.; Ahmad, M.Z.; Castro-Muñoz, R.; Fila, V.
Abstract : Natural gas is one of the most highly used resources, not only as a fuel but also as a raw material for many industrial processes. In addition, it is an environmental friendly fuel due to its lower greenhouse gas emission than that of coal or oil. However, it is a nonrenewable energy source and the quality of the available resources is expected to deplete continuously. In this scenario, membrane technologies can play an important role in the purification of the reduced and contaminated resources, competing with the current technologies owing to their simpler adaptability to different feed compositions, lower energy consumption and investment costs. In this review, the current state of the natural gas sources, including nonconventional resources (tight/shale gas and biogas), is explored, along with the current market status of the conventional natural gas. A comparison between the conventional purification technologies and membrane processes is provided, together with the currently available commercial membranes as well as new materials. Furthermore, the latest materials in research stage are reviewed, pointing out their limitations to the current membranes technologies. Finally, future research trends to overcome the current membrane technology limitations are proposed, and the conclusions are addressed.